2017
DOI: 10.1021/acsami.7b14446
|View full text |Cite
|
Sign up to set email alerts
|

Zincke’s Salt-Substituted Tetraphenylethylenes for Fluorometric Turn-On Detection of Glutathione and Fluorescence Imaging of Cancer Cells

Abstract: In this paper, we report Zincke's salt-substituted tetraphenylethylenes 1a and 1b with Cl and PF as counteranions, respectively. The crystal structure of 1b was determined. Both 1a and 1b are almost nonemissive even in the aggregated states. This is attributed to the photoinduced electron transfer from 2,2-bis(4-methoxyphenyl)-1-phenylvinyl-phenyl unit to 1-(2,4-dinitrophenyl) pyridinium unit within 1a and 1b. The results demonstrate that the emissions of 1a and 1b in aqueous solution can be switched on upon e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(16 citation statements)
references
References 53 publications
(74 reference statements)
1
15
0
Order By: Relevance
“…2c ). 44 Due to the PET process from the TPE unit to the 1-(2,4-dinitrophenyl) pyridinium unit (electron accepter), the probe hardly emits fluorescence even in the aggregate state. The removal of 2,4-dinitrophenyl under light illumination breaks PET processes, resulting in strong green fluorescence emission.…”
Section: Design Of Aie Light-up Probesmentioning
confidence: 99%
“…2c ). 44 Due to the PET process from the TPE unit to the 1-(2,4-dinitrophenyl) pyridinium unit (electron accepter), the probe hardly emits fluorescence even in the aggregate state. The removal of 2,4-dinitrophenyl under light illumination breaks PET processes, resulting in strong green fluorescence emission.…”
Section: Design Of Aie Light-up Probesmentioning
confidence: 99%
“…Zhang et al reported two Zincke's salt substituted tetraphenylethylenes (11 a and 11 b) with Cl À and PF 6 À as counter anions, respectively ( Figure 6). [26] Although they share the same cation structure, the change in counter anion gives rise to different reactivity. 11 a was found to respond to glutathione (GSH) with green fluorescence.…”
Section: Mitochondria-targeted Aiegens For Photodynamic Therapymentioning
confidence: 99%
“…However, after reacting with RTCs, the bromide group can be partially replaced by –SH group, which could restore the fluorescence of KC‐Br probe (Figure 6). At the same time, intramolecular charge transfer (ICT), makes the fluorescence of KC‐SH stronger, so it can be used for the detection of RTCs [15] . In addition, they also found that the free‐NH 2 group can further react with the products substituted by Cys/Hcy to form related Schiff bases, but this kind of reaction will not occur in compound KC‐GSH, so this probe can specifically recognize GSH with high selectivity and sensitivity, and can be used for GSH imaging in living cells, which lays a theoretical foundation for distinguishing similar biological RTCs (Cys/GSH/Hcy).…”
Section: Principle Of the Reaction Between Rtcs And Biosensor Probementioning
confidence: 99%
“…The mechanism of the bimolecular fluorescent probes studied previously was that ICT, leads to serious overlap between probes and the movement of emission bands, which greatly affects the accuracy and resolution of the detection results [6,8,15,39] . In order to solve this problem and improve the resolution of the fluorescent probe, Yang et al .…”
Section: Biological Applications Related To Rtcsmentioning
confidence: 99%
See 1 more Smart Citation